MEDICAL RECORD SYSTEM DESIGN FOR EMPLOYEES COMPUTERIZED PT. EVERADY BATTERY INDONESIA - Dedy Cramer; Eko Hadiyanto, SSI, MM (Jurnal Sistem Informasi, 2001)
Valuable information is the information quickly and accurately. Needed a reliablesystem, with the advancement of existing technologies today computerized the mostappropriate system. Will design a computerized system in the field of medical recordsin PT Eeready Battery Indonesia, with the aim that the management can getinformation quickly and accurately and that stores medical data securely. So with theend result of any information that is useful for decision makers to determine thecompany's policy.